Adoption and diffusion of marine litter clean-up technologies across European seas: Legal, institutional and financial drivers and barriers. (September 2021) - Frantzi, Sofia; Brouwer, Roy; Watkins, Emma; van Beukering, Pieter; Cunha, Maria Conceição; Dijkstra, Hanna; Duijndam, Sem; Jaziri, Hela; Okoli, Ikechukwu Charles; Pantzar, Mia; Rada Cotera, Ignacio; Rehdanz, Katrin; et al.
Abstract: This study reviews existing legal, institutional and policy tools and frameworks, relevant to the introduction and adoption of new marine litter clean-up technologies in two regional European seas, the Mediterranean and the Baltic. A combination of desk studies in six countries bordering the Baltic (Estonia, Germany, Sweden) and the Mediterranean (Greece, Italy, Tunisia), and interviews with experts and stakeholders, is used to identify key drivers and barriers to the adoption and diffusion of marine litter technologies. The main conclusion of the study is that the most influential pieces of legislation relevant to marine litter management are top-down EU policies, often forming the basis of regional and national plans. Moreover, the study finds that several drivers of marine litter technologies may at the same time be critical barriers. These factors include public awareness, consumer behaviour, enforcement of legislation, and the rise of SMEs engaged in recycling and eco-labelling of marine litter. Highlights: Existing legal and policy frameworks for marine litter management are analysed. Marine litter management in European seas is based on post-pollution remedies. European legislation and Regional Action Plans are key drivers. Lack of financial resources is a barrier to adopt marine litter technologies.